Receptor Interaction Profiles of 4-Alkoxy-3,5-Dimethoxy-Phenethylamines (Mescaline Derivatives) and Related Amphetamines - Kolaczynska, Karolina E.; Luethi, Dino; Trachsel, Daniel; Hoener, Marius C.; Liechti, Matthias E. (Frontiers in Pharmacology, 2022)
3,4,5-Trimethoxyphenethylamine (mescaline) is a psychedelic alkaloid found in peyote cactus. Related 4-alkoxy-3,5-dimethoxy-substituted phenethylamines (scalines) and amphetamines (3C-scalines) are reported to induce similarly potent psychedelic effects and are therefore potential novel therapeutics for psychedelic-assisted therapy. Herein, several pharmacologically uninvestigated scalines and 3C-scalines were examined at key monoamine targets in vitro. Binding affinity at human serotonergic 5-HT1A, 5-HT2A, and 5-HT2C, adrenergic 1A and 2A, and dopaminergic D2 receptors, rat and mouse trace amine-associated receptor 1 (TAAR1), and human monoamine transporters were assessed using target specific transfected cells. Furthermore, activation of human 5-HT2A and 5-HT2B receptors, and TAAR1 was examined. Generally, scalines and 3C-scalines bound with weak to moderately high affinity to the 5-HT2A receptor (Ki = 150–12000 nM). 3C-scalines showed a marginal preference for the 5-HT2A vs. the 5-HT2C and 5-HT1A receptors whereas no preference was observed for the scalines. Extending the 4-alkoxy substituent increased 5-HT2A and 5-HT2C receptors binding affinities, and enhanced activation potency and efficacy at the 5-HT2A but not at the 5-HT2B receptor. Introduction of fluorinated 4-alkoxy substituents generally increased 5-HT2A and 5-HT2C receptors binding affinities and increased the activation potency and efficacy at the 5-HT2A and 5-HT2B receptors. Overall, no potent affinity was observed at non-serotonergic targets. As observed for other psychedelics, scalines and 3C-scalines interacted with the 5-HT2A and 5-HT2C receptors and bound with higher affinities (up to 63-fold and 34-fold increase, respectively) when compared to mescaline. The present in vitro data indicates that 3C-P and BZ are likely to induce psychedelic-like psychoactive effects in humans